COVID-19 Vaccination Perception and Attitude among Healthcare Workers in Egypt - Samar Fares; Merihan M. Elmnyer; Shimaa Sabry Mohamed; Radwa Elsayed (SAGE Publishing, 2021)
Introduction COVID-19 pandemic has affected the whole world, especially the frontline worriers. To get shielded through this war, the world is racing to reach and manufacture COVID-19 vaccines. Vaccination hesitancy is one of the significant obstacles to global health. Objectives This study aimed to assess the perception and attitude of healthcare workers in Egypt toward COVID-19 vaccines, acknowledge the determinants of their attitude, and the factors that could increase the acceptance of the vaccine. Methods an observational web-based anonymous survey was conducted on 385 Egyptian healthcare workers in different governorates. The questionnaire-based on Vaccine Hesitancy Survey Questions of the World Health Organization was available in Arabic and English languages and was tested for reliability. Results Regarding vaccination decision, 51% of the participants were undecided, 28% refused, and 21% accepted vaccination. Reasons for vaccine acceptance mainly were risks of COVID-19 (93%), safety (57.5%), and effectiveness (56.25%) of the vaccine. Simultaneously, the reasons for vaccine hesitancy were the absence of enough clinical trials (92.4%) and fear of side effects of the vaccine (91.4%). The leading factor that could increase vaccination acceptance among the participants was to get sufficient and accurate information about the available vaccines. The participants revealed a high mean level of concern for COVID-19 vaccines' safety (3.8 of 5) that differs significantly among the different study groups ( P -value .002). Conclusion Despite the COVID-19 pandemic, only approximately 21% of Egyptian healthcare workers in our study accepted the COVID-19 vaccination. Vaccine hesitancy represents a major barrier to implementing vaccination programs.